Asthma and Risk of Prostate Cancer: A Population-Based Case-Cohort Study in Taiwan. Issue 36 (September 2015) - Su, Yu-Li; Chou, Ching-Lan; Rau, Kun-Ming; Lee, Charles Tzu-Chi
Abstract : Abstract: Several epidemiologic studies in Western countries have examined the association between asthma and prostate cancer risk, but the results have been inconclusive. We investigated this association in a large, nationwide, population-based case-cohort study. Using the Taiwan National Health Insurance Research Database from 1997 to 2008, we collected data from 12, 372 men, including 4124 with asthma and 8248 age-, residence-, and insurance premium-matched control subjects, who were never diagnosed with asthma. Competing risk-adjusted Cox proportional hazards regression was used to calculate the hazard ratios (HRs) and 95% confidence interval (CI) for determining the association between prostate cancer and asthma. During a mean follow-up of 5.05 years (standard deviation, 2.10), there were 74 cases of prostate cancer. The incidence of prostate cancer was 163.0/100, 000 person-years (95% CI: 113.0–228.0) in the asthma patients. Asthma was significantly associated with prostate cancer (HR: 2.36; 95% CI: 1.22–4.57; P  = 0.011) after adjusting for age, residential area, insurance premium, hypertriglyceridemia, hypertension, diabetes mellitus, chronic obstructive pulmonary disease, duration of hospitalization, and mortality. In the subgroup analysis, independent risk factors for prostate cancer among men with asthma were age (HR: 1.09; 95% CI: 1.05–1.21; P  < 0.001) and hypertension (HR: 2.75; 95% CI: 1.24–7.80; P  = 0.047). The results of our study suggest that men with asthma have an increased risk of prostate cancer.